The Affordable Care Act and Health Care Access and Utilization Among White, Asian, and Latino Immigrants in California. Issue 9 (3rd September 2021) - Chu, Jun; Ortega, Alexander N.; Park, Sungchul; Vargas-Bustamante, Arturo; Roby, Dylan H.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: The objective of this study was to examine changes in health care access and utilization for White, Asian, and Latino immigrants associated with the implementation of the Patient Protection and Affordable Care Act (ACA) in California. Study Design: Using the 2011–2013 and 2015–2017 California Health Interview Survey, we examined changes in 2 health care access and 2 utilization measures among 3 immigrant racial/ethnic groups. We estimated the unadjusted and adjusted percentage point changes in the pre-ACA and post-ACA periods. Adjusted estimates were obtained using linear probability models controlling for predisposing, enabling, and need factors. Results: After the ACA was nationally implemented in 2014, rates of insurance increased for non-Latino (NL) White, NL Asian, and Latino immigrant groups in California. Latino immigrants had the largest increase in insurance coverage (14.3 percentage points), followed by NL Asian immigrants (9.9 percentage points) and NL White immigrants (9.2 percentage points). Despite benefitting from the largest increase in insurance coverage, the proportion of insured Latino immigrants was still lower than that of NL White and NL Asian immigrants. Latino immigrants reported a small but significant decrease in the usual source of care (−2.8 percentage points) and an increase in emergency department utilization (2.9 percentage points) after the ACA. No significant changes were found after the ACA in health care access and utilization among NL White and NL Asian immigrants. Conclusions: Insurance coverage increased significantly for these 3 immigrant groups after the ACA. While Latino immigrants had the largest gain in insurance coverage, the proportion of Latino immigrants with insurance remained the lowest among the 3 immigrant racial/ethnic groups.